Підхід до вибору оптимальних характеристик турбіни низького тиску при використанні єдиного газогенератора - Хомилєв, Сергій Олександрович; Кравченко, Ігор Федорович; Попуга, Андрій Іванович (Національний технічний університет "Харківський політехнічний інститут", 2022)
Продемонстровано підхід до концептуального проєктування турбіни низького тиску авіаційного турбогвинтового двигуна на базі єдиного газогенератора. Підхід цікавий тим, що крім коефіцієнта корисної дії, у якості критерію оптимального проєктування використана маса турбіни і маса пального, а також кількість аеродинамічних профілів. Отримано залежність цих параметрів від коефіцієнта аеродинамічного навантаження турбіни, який змінюється шляхом зміни діаметра турбіни в заданих обмеженнях.

An approach to the conceptual design of the low pressure turbine for the aviation turbopropeller engine has been shown. The engine is created on the basis of the single gas generator for the two-engine power plant intended for the average transport aircraft. This approach is of great interest because in addition to the efficiency factor, the mass of the designed turbine, the fuel mass and the number of aerodynamic profile were used as optimal design criteria. The designed turbine includes the two stages and the interturbine transition channel of a diffuser type arranged in front of them. Consideration was given to the four flow parts of the turbine that differ by the diameter and the height selected in the preset limitation range. The gas dynamic efficiency of the interturbine transition channel, gas dynamic efficiency of the after-turbine channel, the strength of the turbine blade of the last stage were taken as the limitations. The dependencies of the efficiency factor, the turbine mass and the number of turbine blades on the turbine aerodynamic load factor were obtained for the four turbine options. The turbine efficiency factor was determined using our own method of one-dimensional gas-dynamic computation. The fuel flow rate was determined using the mathematical engine model. The turbine mass was determined using the parametric method as a function of the aerodynamic load factor and the turbine flow rate factor. The number of aerodynamic profiles was defined using the Zweifel parameter. It was shown that the use of heavy loaded and less loaded low pressure turbines can reduce the take-off weight of the aircraft in spite of an increased fuel flow rate.
Approach to the selection of optimal characteristics for low pressure turbines using a single gas generator
Keywords: аеродинамічне навантаження; силова установка; ККД; маса; aerodynamic load; mass and power plant; efficiency factor